A gold nanostar based multi-functional tumor-targeting nanoplatform for tumor theranostic applications. Issue 35 (17th August 2016) - Wang, Lei; Meng, Dehui; Hao, Yongwei; Hu, Yujie; Niu, Mengya; Zheng, Cuixia; Yanyan, Yin; Li, Dong; Zhang, Panpan; Chang, Junbiao; Zhang, Zhenzhong; Zhang, Yun
Abstract : A gold nanostar based multi-functional tumor-targeting nanoplatform (DOX/GNSTs–PEG/PEI–FA) for tumor theranostic applications. Abstract : Recently, gold nanomaterials have attracted extensive attention due to their unique physical, chemical and biological properties. In this study, gold nanostars (GNSTs) were synthesized first and functionalized with polyethylene glycol (PEG) and polyethylenimine (PEI). We found that GNSTs and their derivatives can be used as radiofrequency (RF) sensitizers for hyperthermia due to their special star shaped structure. Secondly, a multi-functional tumor-targeting drug delivery system DOX/GNSTs–PEG/PEI–FA was constructed. Doxorubicin (DOX) was covalently conjugated onto GNSTs–PEG/PEI by the pH-sensitive hydrazone linkage, and folic acid (FA) was directly conjugated to excess amino groups by amidation reaction. The release profiles of DOX from GNSTs–PEG/PEI–FA showed a strong dependence on the environmental pH value. These in vitro and in vivo results revealed that this drug delivery system has FA tumor-targeting, pH-sensitive controlled release, RF induced hyperthermia and X-ray contrast imaging effects, demonstrating that DOX/GNSTs–PEG/PEI–FA can be used as a potential nano-platform for tumor theranostic applications.